Evaluation of maize, cowpea, cassava and sweet potato intercrop systems. (Journal of Science and Technology, 2016)
Various intercrop systems involving maize , cowpea, cassava and sweet potato grown in the field in the semideciduous forest zone of Ghana were evaluated based on the monetary returns (net incomes) from yields using the 1987 farmgate prices of the crop products. Even though farmgate prices could change with time, the evaluation of the systems in this study would still be valid for as long as he relative importance of the crops (status of the crops with respect to each other) remained unchanged. Maize spaced at 1.0 x 1.0m three plants per hill and intercropped with cassava also spaced at 1.0 x 1.0m in the mane rows was adjudged the best system. It was suggested that this system, commonly practised by peasant farmers in the semideciduous forest zone of Ghana, be encouraged and assisted with the use of fertilizers,o that the same pieces of land can be continuously cropped.